2.53 kW all-fiberized superfluorescent fiber source based on a compact single-stage power-scaling scheme. (24th August 2016) - Xu, Jiangming; Xiao, Hu; Leng, Jinyong; Zhang, Hanwei; Zhou, Pu; Chen, Jinbao
Abstract: In this paper we demonstrate an all-fiberized superfluorescent fiber source that has a maximal output power of 2.53 kW and is based on a single-stage power amplification configuration. The seed source is a broadband-amplified spontaneous emission source with a full output power of 27.6 W. A single-stage dual-clad fiber amplifier is used, in which the maximal optical-to-optical conversion efficiency is 81.47%. A beam quality of M 2   =  1.53 is measured at an output power of 1 kW. At maximum output power, the central wavelength and full width at half maximum linewidth of the amplified light are 1082.08 nm and 6.32 nm, respectively. No conspicuous spike was observed at the stimulated Raman scattering wavelength. The corresponding power fluctuation is 2.97%, which indicates the good power stability of the broadband high-power superfluorescent fiber source (SFS) system. This kilowatt-class high-power all-fiberized SFS system which has high conversion efficiency and good power stability and is based on a compact single-stage power-scaling scheme, is an alternative and competitive solution for industrial precision processes and special stabilized pumping. To the best of our knowledge, this is the highest power SFS ever reported, and the first demonstration of a high-power SFS with a kW-level output power in a compact single-stage power-scaling scheme.